Islamic Law and the Regulation of Human Rights Issues in Separatist Conflicts - Karimullah, Suud Sarim; Sulastri, Sulastri; Kamsi, Kamsi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study reveals how Islamic law and human rights can be a voice of justice in challenging situations, offering exciting and relevant answers for a harmonious future of peace. The research method applied in this study is designed in an integrative and comprehensive manner to explore the relationship between the two in the context of conflict separatism. The study results show that Islamic law and human rights have similar perspectives in respecting religious plurality, avoiding discrimination, and prioritizing peace in dealing with conflict separatism. Both emphasize the importance of understanding the root causes of conflict and seeking comprehensive and sustainable solutions to achieve reconciliation and just peace. In separatism conflicts, Islamic law and human rights also emphasize the importance of social justice, solidarity, education, and accountability as integral parts of conflict management. Both perspectives view that efforts to achieve peace and reconciliation must involve all elements of society, including religious leaders, community leaders, and community organizations, in mediating and promoting peace values. In addition, the harmony between Islamic law and human rights emphasizes the importance of understanding human rights as a universal value that must be upheld by all people, not only in the context of separatism conflicts but also in broader social and political life.